Development of a quantitative, cell-based, high-content screening assay for epidermal growth factor receptor modulators - Wang Jue; Xie Xin (Acta Pharmacologica Sinica; Vol 28, No 10 (October 2007): Acta Pharmacologica Sinica, 2016)
Aim: To develop a robust, cell-based, high-content screening (HCS) assay based on receptor internalization for the identification of novel modulators of the epidermal growth factor receptor (EGFR). Methods: Agonist-induced receptor internalization is part of the signaling cascade of EGFR. Fluorescent-tagged epidermal growth factor (EGF) was used to visualize the internalized receptor-ligand complex. The fluorescent intracellular spots were detected and measured with an ArrayScan HCS reader. Compounds that can competitively bind to EGFR or interfere with EGFR internalization process would result in a reduced number and intensity of intracellular fluorescent spots. This assay was validated, optimized, and applied to a large-scale screening of a library containing 48 000 synthetic compounds. Results: The competition between fluorescent EGF and unlabeled EGF reveals the IC50 of unlabeled EGF is approximately 0.2 nmol/L, which is comparable with other published reports. Thirteen compounds with a relatively high degree of interference with EGFR internalization were identified. One of the compounds was proven to be agonist of the EGFR since it induced phosphorylation of the receptor and extracellular signal-regulated protein kinase (ERK). Conclusion: This automated, objective, and easy-to-use assay provided abundant information, quantitative results, and demonstrated the potential use of HCS methods in searching membrane receptor modulators.